A Dangerous life ([S.l.] Shuiyi Investment Private for and on behalf of Keenan CV, 1988)
The Philippine EDSA revolution comes vividly to life in this epic that dramatizes the turbulent events leading to the downfall of the Marcos dictatorship and the elevation of Corazon Aquino to power, featuring an American journalist reporting in Manila, 1983-1986.
A Southern Star Group presentation in association with the Australian Broadcasting Corp. and Zenith.
This has been an HBO presentation.
VHS.
Philippine producer, Lope V. Juban, Jr. ; written by David Williamson ; produced by Hal McElroy ; directed by Robert Markowitz.
Gary Busey, Rebecca Gilling, Ruben Rustia, Tessie Tomas, Laurice Guillen, Joonee Gamboa.
Keywords: Feature films -- Philippines; Philippines -- History -- Revolution, 1986 -- Drama